2005
DOI: 10.1029/2005jd006019
|View full text |Cite
|
Sign up to set email alerts
|

Control of interannual and longer‐term variability of stratospheric water vapor

Abstract: [1] We use trajectory calculations based on 40-year European Reanalysis (ERA-40) data to predict the water mixing ratio of air entering the stratosphere in the tropics ( [1995][1996][1997][1998][1999][2000][2001][2002], the correlation between model predictions and HALOE water vapor anomalies in the tropical lower stratosphere is r = 0.81, as high as that between HALOE and SAGE II (r = 0.8).The model predictions suggest that the stratospheric quasi-biennial oscillation, El Niño-Southern Oscillation, and possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
221
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(245 citation statements)
references
References 44 publications
21
221
3
Order By: Relevance
“…The correlation is a tropical mean, so reflects transport processes as well. Three dimensional transport affects H 2 O Fueglistaler and Haynes, 2005), but we do expect a broad correlation with mean temperatures (Randel et al, 2004). Two models (MRI, CCSRNIES) lie above this line, which may indicate differences in transport, such that air has bypassed the tropical tropopause.…”
Section: Stratospheric Water Vapormentioning
confidence: 99%
See 2 more Smart Citations
“…The correlation is a tropical mean, so reflects transport processes as well. Three dimensional transport affects H 2 O Fueglistaler and Haynes, 2005), but we do expect a broad correlation with mean temperatures (Randel et al, 2004). Two models (MRI, CCSRNIES) lie above this line, which may indicate differences in transport, such that air has bypassed the tropical tropopause.…”
Section: Stratospheric Water Vapormentioning
confidence: 99%
“…Gettelman and Forster (2002) described a climatology of the TTL, and looked at changes over the observed record from radiosondes, also finding decreases in tropopause pressure (increasing height) with little significant change in the bottom of the TTL (see below). Fueglistaler and Haynes (2005) showed that TTL trajectory analyses could reproduce changes in stratospheric entry water vapor. Santer et al (2003) examined simulated changes in thermal tropopause height and found that they could only explain observations if anthropogenic forcings were included.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2b is a plot of MLS V2.2 stratospheric H 2 O for 15 November 2004, based on data that were accessed from the MLS Website (http://mls.jpl.nasa.gov/). The period of 2004/05 of the MLS data was selected for comparison because the distribution of H 2 O is affected somewhat by the QBO-induced circulations of the lower stratosphere and the tropical winds were changing from a westerly to an easterly QBO phase, as was the case for the LIMS period (Fueglistaler and Haynes, 2005). Although MLS H 2 O extends to near the mesopause, Fig.…”
Section: Lims V6 Zonal Mean Distributions Of H 2 Omentioning
confidence: 99%
“…SWV, for example, induces a reduction of stratospheric ozone concentration (Stenke and Grewe, 2005;Revell et al, 2016), cools the stratosphere (Revell et al, 2012;Forster and Shine, 1999;Maycock et al, 2014) and produces a positive radiative forcing (Solomon et al, 2010). Changes in SWV are mainly driven by tropospherestratosphere exchange (e.g., through deep convection in the tropics; Fueglistaler and Haynes, 2005). However, there is also a chemical contribution to SWV, mostly by oxidation of methane (CH 4 ) and hydrogen gas (H 2 ).…”
Section: Introductionmentioning
confidence: 99%